Policy for Country Contributions for Capacity Building-Implementation of Policy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper provides an update on the implementation of the strengthened country contribution policy for capacity-building (the 'Charging Policy') and informs the Executive Board of management's intentions to delay the date of effectiveness of some features of the Charging Policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund Capacity-Building; Fund; PP; Practice Change